2016
DOI: 10.17706/jsw.11.4.347-361
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Testing for Web Applications: A Literature Survey Presented

Abstract: Abstract:The World Wide Web has a great impact in the world of computing. Testing of web applications is becoming more challenging task with the tremendous growth, distributed nature, dynamic nature and heterogeneity of web applications. With the growing complexity and usage of web applications, there is a need of rigorous testing techniques for producing reliable applications. Model-based testing (MBT) is a promising paradigm for generating test cases from models of the system under test (SUT). Different tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Hasan Javed and Nasir Mehmood Minhas [3] presented an SLR in which MBT approaches were identified, analyzed areas in which approaches were addressed, and defined tools supporting these techniques. But not discuss the challenges and gaps of MBT for web application testing.…”
Section: Farooq Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Hasan Javed and Nasir Mehmood Minhas [3] presented an SLR in which MBT approaches were identified, analyzed areas in which approaches were addressed, and defined tools supporting these techniques. But not discuss the challenges and gaps of MBT for web application testing.…”
Section: Farooq Et Almentioning
confidence: 99%
“…Gaps are identified for future researchers and aim for further enhancement in this research area [3].…”
Section: ) Question 3 Assessment What Are the Challenges And Gaps Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…FSM is commonly used to model system behaviours in MBT and is utilized in this research. Javed, Minhas [18] conducted a systematic literature review (SLR) study of MBT for web app and they concluded that majority of the identified MBT approaches are based on FSM and several other behavioural models like activity diagram, state diagram and extended FSM (EFSM). Furthermore, Sabbaghi and Keyvanpour [19] conducted a study to review the most used state-based models in MBT.…”
Section: Model-based Testingmentioning
confidence: 99%